Amending the Anisotropy Barrier and Luminescence Behavior of Heterometallic Trinuclear Linear [MIILnIIIMII] (LnIII=Gd, Tb, Dy; MII=Mg/Zn) Complexes by Change from Divalent Paramagnetic to Diamagnetic Metal Ions. Issue 17 (13th March 2015) - Das, Sourav; Bejoymohandas, K. S.; Dey, Atanu; Biswas, Sourav; Reddy, M. L. P.; Morales, Roser; Ruiz, Eliseo; Titos‐Padilla, Silvia; Colacio, Enrique; Chandrasekhar, Vadapalli
Abstract The sequential reaction of a multisite coordinating compartmental ligand [2‐(2‐hydroxy‐3‐(hydroxymethyl)‐5‐methylbenzylideneamino)‐2‐methylpropane‐1, 3‐diol] (LH4) with appropriate lanthanide salts followed by the addition of [Mg(NO3)2]⋅6 H2O or [Zn(NO3)2]⋅6 H2O in a 4:1:2 stoichiometric ratio in the presence of triethylamine affords a series of isostructural heterometallic trinuclear complexes containing [Mg2Ln]3+ (Ln=Dy, Gd, and Tb) and [Zn2Ln]3+ (Ln=Dy, Gd, and Tb) cores. The formation of these complexes is demonstrated by X‐ray crystallography as well as ESI‐MS spectra. All complexes are isostructural possessing a linear trimetallic core with a central lanthanide ion. The comprehensive studies discussed involve the synthesis, structure, magnetism, and photophysical properties on this family of trinuclear [Mg2Ln]3+ and [Zn2Ln]3+ heterometallic complexes. [Mg2Dy]3+ and [Zn2Dy]3+ show slow relaxation of the magnetization below 12 K under zero applied direct current (dc) field, but without reaching a neat maximum, which is due to the overlapping with a faster quantum tunneling relaxation mediated through dipole–dipole and hyperfine interactions. Under a small applied dc field of 1000 Oe, the quantum tunneling is almost suppressed and temperature and frequency dependent peaks are observed, thus confirming the single‐molecule magnet behavior of complexes [Mg2Dy]3+ and [Zn2Dy]3+.